Koncepcja czteropoziomowego kontekstu Ruth Wodak jako wyraz interdyscyplinarności w analizie dyskursu - Kopińska, Violetta (Kultura-Społeczeństwo-Edukacja, 2019)
The concept of four-level context by Ruth Wodak is to provide triangulation and minimize the risk of being biased. Simultaneously the analysis of this concept in combination with the research programme of HDA is an expression of interdisciplinarity’s importance in this approach. One should notice that interdisciplinarity is not an aim itself and it is a subject to limitations. The most specific limitations are those which result from triangulation on the interdiscursive level.